2018
DOI: 10.1002/jso.25263
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo indocyanine green fluorescence imaging for the detection of lymph node involvement in advanced‐stage ovarian cancer

Abstract: Background and objectives The aim of this study was to evaluate the role of indocyanine green (ICG) fluorescence imaging (FI) for the ex vivo detection of metastatic lymph nodes (LNs) in advanced stage ovarian cancer (AOC). Methods Paraffin‐embedded LNs from patients included in a previous ICG‐FI study (Protocol NCT01834469) were further assessed for fluorescence. Intravenous injection of ICG was delivered intraoperatively. Tumor‐to‐background ratios (TBRs) were calculated. Results A total of 675 LNs from 19 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…in patients who underwent lymphadenectomy for the nodal relapse of head and neck cancer ( 53 ). Our group confirmed their observation in 2016 in a series of 11 patients who had undergone cervical lymphadenectomy for primary and relapsing head and neck cancer ( 54 ) but also reported such accumulation of ICG in metastatic LNs in cases of colorectal and ovarian cancer ( 55 57 ).…”
Section: Discussionsupporting
confidence: 88%
“…in patients who underwent lymphadenectomy for the nodal relapse of head and neck cancer ( 53 ). Our group confirmed their observation in 2016 in a series of 11 patients who had undergone cervical lymphadenectomy for primary and relapsing head and neck cancer ( 54 ) but also reported such accumulation of ICG in metastatic LNs in cases of colorectal and ovarian cancer ( 55 57 ).…”
Section: Discussionsupporting
confidence: 88%
“…Second, timing is a major concern when using ICG-FI for tumoral detection and the best interval between ICG IV injection and imaging remains to be defined. In our study, the median time observed between ICG injection and the resection of the operative specimen was 46 min, corresponding to the optimal delay for ICG-FI reported in the literature in breast tumors and other oncological conditions [13e15, 18,20,34]. Third, the imaging system used in our study, which does not have an appropriated sized camera head for tumor bed exploration and does not allow dual imaging (combined view) with white light in color and NIR, which should rule out the background noise issues.…”
Section: Discussionmentioning
confidence: 55%
“…For objective fluorescence intensity calculation, we used, as reported in our previous studies, a semi-quantitative analysis of the fluorescence intensity using signal-to-background fluorescence ratio (SBR) on intraoperative recorded videos and tumor to background ratio (TBR) on videos recorded in the pathology department. These images were correlated with the final anatomoepathological reports [13,18,20].…”
Section: Semi-quantitative Fluorescence Intensity Analysis (Primary Bc and Margins)mentioning
confidence: 99%
See 1 more Smart Citation
“…To improve nodal yield and to increase detection of small LNs, fat clearance can be performed 19 , but this technique requires a chemical agent to dissolve the fat tissue around the LNs, and thus is time consuming, expensive and potentially hazardous. Local or intravenous/intra-arterial injections of methylene blue and indocyanine green have been used to improve LN identification at pathology, but due to poor tumor specificity this has never become routinely implemented; sensitivities and specificities achieved with this approach vary between 52–94% and 76–78%, respectively 2022 . Most importantly, none of the current techniques discriminates between metastatic LNs and benign LNs.…”
Section: Discussionmentioning
confidence: 99%